PENDIDIKAN ISLAM DALAM MEMBENTUK KARAKTER BERADAB MANUSIA MENURUT ADIAN HUSAINI - Mudhoffar Mudhoffar; Roihanah (Jurnal Penelitian Ilmiah INTAJ, 2021)
Education is a conscious and planned effort to develop its potential to become skilled, intelligent, moral human beings, and can use their talents for themselves, society, nation, and state. This study aims to identify Islamic education in shaping civilized human character. The method used in this study is a qualitative method which produces descriptive data in the form of written or spoken words from people who can be observed. Sources of data in this study are primary data and secondary data. This research is qualitative research with a Historical-Phyosophical approach which aims to identify Islamic education in shaping human and civilized character. From the results of the study, it was concluded that, according to Adian Husaini, in shaping human and civilized character, namely character education given to Muslim students (in particular), character education must be based on monotheism and ta'dib. This will later distinguish between the character possessed by other nations, and the character possessed by the Indonesian nation, especially in the Muslim community.